Impact of enhanced recovery after surgery with preoperative whey protein-infused carbohydrate loading and postoperative early oral feeding among surgical gynecologic cancer patients: an open-labelled randomized controlled trial - Ho, Chiou Yi; Ibrahim, Zuriati; Abu Zaid, Zalina; Mat Daud, Zulfitri 'Azuan; Md. Yusop, Nor Baizura; Omar, Jamil; Mohd Abas, Mohd Norazam; Abdul Rahman, Zuwariah; Jamhuri, Norshariza (MDPI, 2020)
Enhanced Recovery after Surgery (ERAS) with sole carbohydrate (CHO) loading and postoperative early oral feeding (POEOF) shortened the length of postoperative (PO) hospital stays (LPOHS) without increasing complications. This study aimed to examine the impact of ERAS with preoperative whey protein-infused CHO loading and POEOF among surgical gynecologic cancer (GC) patients. There were 62 subjects in the intervention group (CHO-P), which received preoperative whey protein-infused CHO loading and POEOF; and 56 subjects formed the control group (CO), which was given usual care. The mean age was 49.5 ± 12.2 years (CHO-P) and 51.2 ± 11.9 years (CO). The trial found significant positive results which included shorter LPOHS (78.13 ± 33.05 vs. 99.49 ± 22.54 h); a lower readmission rate within one month PO (6% vs. 16%); lower weight loss (−0.3 ± 2.3 kg vs. −2.1 ± 2.3 kg); a lower C-reactive protein–albumin ratio (0.3 ± 1.2 vs. 1.1 ± 2.6); preserved muscle mass (0.4 ± 1.7 kg vs. −0.7 ± 2.6 kg); and better handgrip strength (0.6 ± 4.3 kg vs. −1.9 ± 4.7 kg) among CHO-P as compared with CO. However, there was no significant difference in mid-upper arm circumference and serum albumin level upon discharge. ERAS with preoperative whey protein-infused CHO loading and POEOF assured better PO outcomes.